ANALISIS SIFAT FISIKOKIMIA DAN ORGANOLEPTIK CAKE DENGAN RASIO TAPAI JAGUNG (Zea mays L.) DAN TAPAI SINGKONG BERBEDA - Azzari, Rayhana; Davi, Mazarina; Wibowotomo, Budi (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2024)
Cake is one product bakery loved by the community. One of the variants cake what is known is cake cassava tapai. Currently, corn tapai is a fermented product that is not widely known by thepublic. The content contained in corn tapai has the potential to enrich the nutrition of a processed food. This research aims to analyze the physicochemical and organoleptic propertiescake ratio of corn tapai and cassava tapai. The research method used was an experiment using a Completely Randomized Design (CRD) with two repetitions. The aim of this research is todetermine chemical properties (food fiber, protein, fat, water, ash and carbohydrates), physical properties (volume and color), and hedonic properties (taste, texture, color and aroma) ratiocake corn tapai and cassava tapai 50:50, 75:25 and 100:0. Data were analyzed using ANOVA with further tests Duncan Multiple Range Test (DMRT). The research results show cake ratiocorn tapai and cassava tapai 100:0 have the highest chemical properties in terms of food fiber, protein, fat, ash and carbohydrate levels respectively at 9.689%, 5.460%, 11.522%, 1.346% and52.386% but the lowest at water content at 29.258%. Physical properties volume highest on ratio cake corn tapai and cassava tapai 50:50 amounting to 304,856 cm3. Physical properties ofratio colorscake corn tapai and cassava tapai 100:0 L (77.19), a (5.65), b(57.26). The highest hedonic level has a ratio of 100:0 for taste, texture, color and aroma, respectively 4.48, 4.26,4.38, 4.38. The most preferred ratio of the hedonic test is the ratio cake the ratio of corn tapai and cassava tapai is 100:0 in terms of taste, texture, color and aroma. It can be concluded thatthe ratio of corn tapai and cassava tapai provides significant differences in chemical, physical and organoleptic properties cake.